Disseminated peritoneal leiomyomatosis: an unusual presentation of intra-abdominal lesion mimicking disseminated malignancy - Soni, Sweta; Pareek, Puneet; Narayan, Satya (Medicine and Pharmacy Reports, 2020)
Leiomyoma are commonly seen as benign smooth muscle tumors of the uterus. Smooth muscle tumors with unusual growth pattern are rare and include 3 primary neoplasms: intravenous leiomyomatosis (IVL), benign metastasizing leiomyoma (BML) and disseminated peritoneal leiomyomatosis (DPL). DPL is a rare benign disease, often giving the appearance of metastatic ovarian or peritoneal carcinoma. It is a disease that predominately affects women at their reproductive age. The risk of malignant transformation is 2-5%. There are no standard treatment guidelines for the management of the DPL. The unusual presentation of the disease delays the diagnosis or is often misdiagnosed and thus over treated, which may lead to increased morbidity and mortality. Therefore careful consideration and high index of suspicion is required for the proper management of such cases.